Fotodegradasi High Density Polyethylene Yang Mengandung Aditif Okso-Biodegradasi - Asriza, Ristika O.; Pitulima, Janiar (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
High Density Polyethylene (HDPE) is a type of plastic that widely used for packaging because it has good mechanical properties. HDPE is naturally non-biodegradable, and the consequence it will increase plastic waste that will damage the environment. To increase their biodegradability, it is necessary to add an oxo-biodegradation additive in the form of a stearate metal compound. This oxo-biodegradation additive is a chromophore that can absorb UV light. Polyethylene oxo-biodegradation films are prepared by mixing HDPE and cobalt stearate to homogeneous on various compositions. To know the effect of adding cobalt stearate into HDPE has done by photodegradation process. The polyethylene oxo-biodegradation film was given irradiation using UV light in the wavelength range 280-300 nm at room temperature for 10 days. After irradiation, in the ATR spectrum shows an absorption peak at 1712 cm-1 wavenumber indicatied the presence of a carbonyl group with a stronger intensity. The higher concentration of cobalt stearate added in HDPE, increases the peak intensity of carbonyl group. This is due to the increasing number of chromophores from cobalt stearate that can absorb UV light, the faster the breakdown of HDPE chains into small fragments so that HDPE is rapidly degraded in nature.